The effect of mindfulness on service encounter quality - Wang, Emma Junhong; Berthon, Pierre R.; Bechwati, Nada Nasr (Journal of Services Marketing, 2020)
Purpose This paper aims to explore the effect of employees’ state mindfulness, a short period of mindful presence, on the quality of the service they provide in a service encounter. Design/methodology/approach Three studies are conducted. A pilot study explores the relationship between state mindfulness and service encounter quality. Experiment 1 examines whether a 15-min mindfulness exercise results in an increase in service employees’ state mindfulness. Experiment 2 tests whether induced state mindfulness produces higher service quality and whether a reminding technique can prolong state mindfulness between service encounters. Findings The results demonstrate the following. First, that more mindful employees provide better service quality. Second, that a short, easily implemented, mindfulness exercise can reliably increase employees’ state mindfulness. Third, induced mindfulness has an impact on subsequent service quality in terms of reliability, assurance, empathy and responsiveness. These effects persist regardless of the service encounter structure (high vs low structure) or the degree of emotional labor involved (high vs low emotionally charged). Finally, the reminding technique developed as part of this research suggests that state mindfulness can be maintained between service encounters. Research limitations/implications As simulated (programmed) customers are used, independent evaluators to assess service quality are used. Service providers in this study are college students; future field studies should consider a wider range of service providers. The research focuses on state mindfulness; exploration of trait mindfulness offers future research opportunities. Originality/value To the best of the authors’ knowledge, this research is the first to empirically examine the link between mindfulness and service quality. It shows that mindfulness can be induced, and through a reminding technique be maintained, and improve service quality across service interactions. This is a powerful finding for marketing managers, for it offers a new method to enhance service provision. Moreover, this research implies that the increase in service quality is likely to be accompanied by reduced job burnout: a double win for employees, employers and customers.
7 citations (Crossref) [2023-10-31]
Keywords: Emotional labor; Induced state mindfulness; Mindfulness; Service encounter quality; Service encounter structure; dept.mkt; peer-reviewed

Sensemaking and sustainability: a sensemaking perspective on the ethical use of big data in marketing strategizing - Wang, Emma (Junhong); Berthon, Pierre; Su, Yiran (Sustainable Development Seen Through the Lenses of Ethnoeconomics and the Circular Economy, 2024)
Despite the ethical concerns over the datafication and surveillance of individuals and groups, companies are making ever greater investments in big data. The assumptions underpinning this movement are: (1) organizations are passive implementers of big data—more data is the inevitable consequence of technology and a competitive necessity for business, (2) more data offers a more objective and accurate picture of reality and (3) more data enables better prediction. We argue that this perspective is strategically unsustainable and abdicates ethical responsibility.
Keywords: Big Data; Organization; Sensemaking; Strategizing; Sustainability; dept.mrk

Building positive experiences for sustainable development - Wang, Zheni; Zhu, Guorong; Zhang, Mengyi; Wang, Emma; Lv, Shuangning; Zheng, Jiawei; Shen, Yan; Steckler, Erica (Academy of Management Proceedings, 2025)
Keywords: Creativity; Face (sociological concept); Grounded theory; Stakeholder; Stakeholder engagement; Sustainability; Sustainable development; Work (physics); dept.mgt; dept.mrk